Investigating thermal properties of Nanoparticle Dispersed Paraffin (NDP) as phase change material for thermal energy storage. (2021) - Manoj Kumar, P.; Mylsamy, K.; Prakash, K.B.; Nithish, M.; Anandkumar, R.
Abstract: Nano sized particles have been used in variety of applications due to their unique behavior and distinguished properties at the nano-scale. In this present work, nanoparticles of zinc oxide (in a proportion of 0.5%, 1.0% and 2.0% of weight) were embedded with the commercial grade paraffin and samples were prepared. Then, thermal characteristics of all the samples were studied with the help of different instruments to find its improvement for using them as thermal energy storage elements. The chemical stability was examined with Fourier transform infrared spectrometer (FT-IR) and thermal stability was studied with thermogravimetric analyzer (TGA). Further, thermal conductivity was analyzed using thermal properties analyzer. The results proved that the zinc oxide nanoparticles dispersed and distributed inside the paraffin without distressing its chemical structure. Further, the nanoparticles amended the thermal stability of the paraffin to the prodigious extend and enhanced thermal conductivity of the paraffin up to 41.67% with 2.0 wt% of nano-ZnO particles.